2017
DOI: 10.4103/ijn.ijn_71_17
|View full text |Cite
|
Sign up to set email alerts
|

Role of gut-derived uremic toxins on oxidative stress and inflammation in patients with chronic kidney disease

Abstract: Several cardiovascular disease (CVD) risk factors have been identified among patients with chronic kidney disease (CKD). Gut-derived uremic toxins (GDUT) are important modifiable contributors in this respect. There are very few Indian studies on GDUT changes in CKD. One hundred and twenty patients older than 18 years diagnosed with CKD were enrolled along with forty healthy subjects. The patients were classified into three groups of forty patients based on stage of CKD. Indoxyl sulfate (IS), para cresyl sulfat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 33 publications
(39 reference statements)
1
15
0
Order By: Relevance
“…These results are in line with a different study showing higher TAC in a rat model of AKI than in sham-operated animals [52]. Another study involving CKD patients has shown higher FRAP concentrations in patients than in controls [53]. In addition, urinary FRAP levels were also elevated in 5/6 Nex, confirming the situation observed in plasma.…”
Section: Discussionsupporting
confidence: 88%
“…These results are in line with a different study showing higher TAC in a rat model of AKI than in sham-operated animals [52]. Another study involving CKD patients has shown higher FRAP concentrations in patients than in controls [53]. In addition, urinary FRAP levels were also elevated in 5/6 Nex, confirming the situation observed in plasma.…”
Section: Discussionsupporting
confidence: 88%
“…By contrast, in advanced CKD, the elevated levels of circulating UTs may promote atherosclerotic calcification and be responsible for the development of Monckeberg’s medial calcification. Several UTs (notably indoxyl sulphate (IS) and paracresyl sulphate (pCS)) display pro-inflammatory properties, and their serum concentrations are correlated with inflammatory markers in patients with CKD [103]. Some of these inflammatory markers (such as TNF-α, IL-6 and IL-1β) are themselves classified as UTs [104].…”
Section: The Impact Of Ckd On Macrophage Functions: Consequences Fmentioning
confidence: 99%
“…Here we review gut-derived, protein-bound uremic toxins, separating them into two categories: (1) diet-ingested toxins and (2) toxins generated by gut microbial metabolism. Both PBUT categories impact gut microflora composition, and the intake, intestinal absorption, and serum levels of these toxins are altered with each progressing stage of kidney disease [ 20 ]. We outline the derivation and pathological mechanisms of each class of gut-derived PBUT, as well as their relationship to the gut microbiota, and we present recent approaches to reduce PBUT levels by targeting the gut microbiome.…”
Section: Introductionmentioning
confidence: 99%